OPTIMIZATION OF OCCUPATIONAL HEALTH AND SAFETY IMPLEMENTATION IN THE AGRICULTURE FACULTY LABORATORY OF SRIWIJAYA UNIVERSITY - Nyayu Nurul Husna; Naomi Tosani; Neny Afridayanti (Jurnal Kesehatan Masyarakat, 2023)
Working in a laboratory is inextricably linked to the various potential hazards. The majority of workplace accidents are the result of unsafe behavior, with the remainder being the result of unsafe working conditions. The purpose of this study was to determine the extent of the application of occupational safety and health in laboratories within the Faculty of Agriculture, Sriwijaya University and to find out the obstacles to the application of occupational safety and health. This research is a descriptive study with a qualitative approach. The data was collected by means of interview, observation and documentation, then data analysis was carried out which included data collection, data reduction, data presentation and data verification. This research was conducted in nine laboratories in the Faculty of Agriculture, namely the Agricultural Cultivation Laboratory, Agricultural Product Technology Laboratory, Plant Pest and Disease Laboratory, Soil Laboratory, Aquaculture Laboratory, Agricultural Product Technology Laboratory, Animal Nutrition and Feed Laboratory. Based on the results of the research that has been obtained, it can be concluded that the overall percentage of questionnaire results is 54% who answered yes and 46% answered no. This means that most of the Agricultural Faculty laboratories have not implemented OHS properly.Researchers hope that this research can optimize the application of safety and occupational health in the laboratory so that it can reduce the number of work accidents in the laboratory.